Effect of high pressure homogenization and high power ultrasound on some physical properties of tomato juices with different concentration levels. (November 2017) - Bot, Francesca; Calligaris, Sonia; Cortella, Giovanni; Nocera, Francesco; Peressini, Donatella; Anese, Monica
Abstract: The effect of high pressure homogenization (HPH) and ultrasound (US) on rheological properties, color, precipitate weight ratio, pectin esterification degree and cell integrity of tomato juices with different soluble solids content (5.0, 7.5, 10.0 °Brix) was studied. Samples were subjected to HPH up to 150 MPa or US up to 30 min. The energy efficiency associated to the processes was also evaluated. Results showed that stress type and product concentration influenced the changes of tomato juice physical properties. In particular, HPH and US treatments were responsible for higher G′ and consistency of processed tomato juices than untreated samples. Increases in sample rheological properties were comparable for the 5.0 and 7.5 °Brix treated HPH and US samples, whereas HPH was more effective than US in the case of 10.0 °Brix sample. These changes were in agreement with other indexes, i.e. precipitate weight ratio increase and cell integrity decrease, and were attributed to stronger of inter-particle interactions. The process energy efficiency showed that lower energy was involved in HPH in comparison to US. Highlights: HPH and US caused physical modifications in tomato juice. Tomato juice concentration affected process performances. HPH caused greater changes in physical properties of 10.0 °Brix tomato juice than US. HPH and US were compared in terms of energy efficiency.